Dynamic oscillatory shear testing of foods — selected applications - Gunasekaran, Sundaram; Ak, M. Mehmet (Elsevier BV, 2000)
Abstract An ideal solid material will respond to an applied load by deforming finitely and recovering that deformation upon removal of the load. Such a response is called “elastic”. Ideal elastic materials obey Hooke's law, which describes a direct proportionality between the stress (σ) and strain (γ) via a proportionality constant called modulus (G), i.e., σ=Gγ. An ideal fluid will deform and continue to deform as long as the load is applied. The material will not recover from its deformation when the load is removed. This response is called “viscous”. The flow of simple viscous materials is described by Newton's law, which constitutes a direct proportionality between the shear stress and the shear rate ( γ ), i.e., σ=η γ . The proportionality constant η is called the shear viscosity. From energy considerations, elastic behavior represents complete recovery of energy expended during deformation, whereas viscous flow represents complete loss of energy as all the energy supplied during deformation is dissipated as heat. Ideal elastic and ideal viscous behaviors present two extreme responses of materials to external stresses. As the terms imply, these are only applicable for “ideal” materials. Real materials, however, exhibit a wide array of responses between viscous and elastic. Most materials exhibit some viscous and some elastic behavior simultaneously and are called “viscoelastic”. Almost all foods, both liquid and solid, belong to this group. The viscoelastic properties of materials are determined by transient or dynamic methods. The transient methods include stress relaxation (application of constant and instantaneous strain and measuring decaying stress with respect to time) and creep (application of constant and instantaneous stress and measuring increasing strain with time). Though such methods are fairly easy to perform, there are several limitations. Major among them is that the material response cannot be determined as a function of frequency.